2010
DOI: 10.1007/s00127-010-0266-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceived need for mental health care and barriers to care in the Netherlands and Australia

Abstract: PurposeThis study of Australian and Dutch people with anxiety or depressive disorder aims to examine people’s perceived needs and barriers to care, and to identify possible similarities and differences.MethodsData from the Australian National Survey of Mental Health and Well-Being and the Netherlands Study of Depression and Anxiety were combined into one data set. The Perceived Need for Care Questionnaire was taken in both studies. Logistic regression analyses were performed to check if similarities or differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 37 publications
5
64
2
4
Order By: Relevance
“…Nelson and Park (2006) have suggested that the elevated levels of unmet need among users of mental health care might be due to the increasing awareness of the limitations of these services, but this explanation has never been tested empirically. In line with this, a recent study in the Netherlands and Australia has shown that the thought that professional care would not help is the second most cited reason for not seeking care (Prins et al, 2011).…”
Section: Introductionmentioning
confidence: 64%
“…Nelson and Park (2006) have suggested that the elevated levels of unmet need among users of mental health care might be due to the increasing awareness of the limitations of these services, but this explanation has never been tested empirically. In line with this, a recent study in the Netherlands and Australia has shown that the thought that professional care would not help is the second most cited reason for not seeking care (Prins et al, 2011).…”
Section: Introductionmentioning
confidence: 64%
“…The types of needs assessed related to the following: information on mental disorders, and on the available treatments or services; medication; psychotherapy or counselling; and psychosocial interventions (that is, help related to housing, interventions). The PNCQ has been used extensively in populations with common mental disorders [8][9][10][11][12][13][14][15][16][17][18][19] and has demonstrated acceptable reliability and validity, with interrater reliabilities generally exceeding kappas of 0.6 and a multi-trait, multi-method approach lending support to the instrument's construct validity. 7,31 Three somewhat different versions of the PNCQ were used, depending on the time of execution.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] In 2000, Meadows et al 7 created a detailed questionnaire (that is, the PNCQ) to assess needs for care from the patient's point of view. The PNCQ has been used previously in adults suffering from common mental health disorders, [8][9][10][11][12][13][14][15][16][17][18][19] with studies revealing that, in industrialized countries, between 45% to 75% of patients with anxiety and depressive disorders consulting in primary care report that their needs are only partially met or completely unmet. 12,13,16,20 Rates of met and unmet needs for care also vary by the type of perceived needs examined.…”
mentioning
confidence: 99%
“…Participants were selected for interview based on their level of psychological distress using Kessler 10 scores [26] in order to obtain a reasonable representation in each category of psychological distress. Interviews were offered to 100% of those with a high-range score (25+), 75% of those with a moderate-range score (16)(17)(18)(19)(20)(21)(22)(23)(24), and one-sixth of those scoring in the low range (10)(11)(12)(13)(14)(15). A total of 636 (73%) participants completed a WMH-CIDI-3.0.…”
Section: Participantsmentioning
confidence: 99%
“…poor understanding of mental disorders and the stigma surrounding these conditions), and societal values [10]. Socio-demographic characteristics are frequently correlated with service utilisation, such that females, older persons, those previously married, those less educated, and those with a primary and co-occurring mental health disorder are more likely to utilise services [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%